Ethosomal Drug Delivery System: A Newer Approach - Kalra, Naresh; Choudhary, Suresh; Arora, Pankaj; Arora, Namita (Asian Journal of Pharmaceutical Research and Development, 2020)
The transdermal drug delivery system is a technique that provides advantages over conventional administration routes such as intravenous ororal route. Ethosomes are non-invasive delivery carriers that enables drugs to reach the deep skin layers and the systemic circulation. Ethosomal systems are conceptually sophisticated, they are simple in their preparation, safe for use a combination that can highly expand their application. Ethosomes are soft, malleable vesicles tailored for enhanced delivery of active agents. The size range of ethosomes may vary from tens of nanometres (nm) to microns (µm). Ethosomes formulation are convenient for use & harmlessness to skin.